2012
DOI: 10.3141/2316-11
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Simulation Assignment Model for Pedestrian Movements in Crowded Networks

Abstract: The planning of crowded pedestrian facilities involves providing adequate capacity for all walkways, as well as designing effective schemes for crowd management. PEDSTREAM is a mesoscopic simulation-based dynamic trip assignment model for large-scale pedestrian networks. The model can represent temporospatial distribution of pedestrians and associated service levels over the network and can predict pedestrian responses to changes in design, operational conditions, and crowd management strategies. The model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In order to analyse the pedestrian movement in this area, it's important to consider factors such as the width and length of the lane (35m width and ≈ 10 km) [21], the number of people moving through it at any given time (500,000 pilgrims/hour) [23], and the speed or flow of the pedestrian traffic (depends on group classification shown in Figure 4). Observing these elements can provide valuable insights into the behaviour of the pilgrims and help identifying any areas where improvements could be made [24].…”
Section: Data Collectionmentioning
confidence: 99%
“…In order to analyse the pedestrian movement in this area, it's important to consider factors such as the width and length of the lane (35m width and ≈ 10 km) [21], the number of people moving through it at any given time (500,000 pilgrims/hour) [23], and the speed or flow of the pedestrian traffic (depends on group classification shown in Figure 4). Observing these elements can provide valuable insights into the behaviour of the pilgrims and help identifying any areas where improvements could be made [24].…”
Section: Data Collectionmentioning
confidence: 99%
“…Hence, the existing facilities at Hajj areas turn more congested due to overcrowding of pilgrims and causing limited pedestrian movements (Owaidah, et.al (2019). Abdelghany et al (2012), estimated that the peak pedestrian flow rate between Arafat and Muzdalifah had reached 500,000 pilgrims per hour and expected to increase by years. Friberg & Hjelm (2015), emphasized that pedestrian overcrowding may lead to rushes, traffic and human bottlenecks, counter flows, stop-and-go waves, crowd turbulence, and panic among the pilgrims.…”
Section: Understanding Crowd Management In the Context Of Hajjmentioning
confidence: 99%
“…These models adopt different modeling approaches to represent the pedestrians' behavior including destination and route choice, adjustment of walking trajectory, walking speed, congestion aversion, and collision avoidance. These approaches include, for example, CA models, [45][46][47][48][49][50][51][52][53][54][55] lattice gas models, [56][57][58][59] social force models, [60][61][62][63][64] agent-based models, [65][66][67][68][69][70][71][72] fluid-dynamic models, 23,[73][74][75] and mesoscopic models. 52 A recent comparison among these techniques can be found in Duives et al 44 They concluded that the models can roughly be divided into slow but highly precise microscopic modeling attempts and very fast but behaviorally questionable macroscopic modeling attempts.…”
Section: Simulation-based Studiesmentioning
confidence: 99%